Student's profile of self-compassion at senior high school and implications for guidance and counseling - Ramadhan, Restu Afdal; Yusuf, Syamsu; Solehuddin, M.; Saripah, Ipah (Universitas Negeri Yogyakarta, 2024)
Adolescence is a phase filled with uncertainty and confusion, especially when adolescents face academic failures, personal achievements, family pressures and physical images that cause emotional stress and emotional instability that affect adolescents' self-esteem. To overcome these challenges, adolescents must develop self-compassion, which is a good attitude towards themselves in dealing with failure and achieving psychological well-being. The purpose of this study was to determine the self-compassion profile of adolescents in senior high school. The research method used a quantitative survey design with 105 samples of senior high school adolescents (aged 16-17 years, the majority of Sundanese ethnicity, residing in rural areas). The research showed that adolescents' self-compassion was classified as moderate (95% = 100), high (1% = 1) and low (4% = 4). This condition coveyed that adolescents hadmoderate self-compassion although it was not too high. Descriptive test results showed a Cronbach Alpha of 0.415 in the moderate category with male adolescent having higher levels of self-compassion (mean 54.5) compared to female adolescent (mean 50.8). This finding highlights the importance of adolescents to master self-compassion in promoting emotional stability and resilience when facing any failure. Then the need for guidance and counseling programs focusingon developing self-compassion such as mindful self-compassion.